Celebration of the 400th anniversary of the Lithuanian book - Žukas, Vladas (Knygotyra, 1988)
In 1947, Lithuania celebrated the 400th anniversary of the first Lithuanian book, M. Mažvydas's Cathechismus, published in 1547. During this celebration, scientific conferences and book exhibitions were organized, and several significant works devoted to the anniversary were published.Among these was one of the most artistic editions: "The First Lithuanian Book" (a photographic text of the Cathechismus and its transliteration in Latin letters, with articles by J. Kruopas and illuminations by M. Bulakas). In the collection of articles "Ancient Lithuanian Book," significant research in the history of the book and literature was presented, including K. Korsakas's "The First Lithuanian Book," V. Mykolaitis's "Artistic Elements in the Works of Mažvydas and His Contemporaries," P. Galaunė's "Artistic Design of Mažvydas's Book," and V. Abramavičius's "Printing-Offices of Ancient Lithuanian Books." These works addressed issues such as the conditions under which the first Lithuanian book was published, its significance, the date of its publication, its intended audience, authorship and collaboration issues, and analyses of the published texts from linguistic, literary, pedagogical, and ethnographic perspectives, as well as typographical particularities.Some material from the jubilee celebration, such as reports from conferences, was published in the "Directory of the Academy of Sciences of the Lithuanian SSR" (1948, vol. 2). Jubilee reports by V. Mykolaitis, "The First Lithuanian Book" (1948), and K. Korsakas, "Development of Lithuanian Book over 400 Years" (1948), were published separately. During the anniversary year, the first Lithuanian book and other works by M. Mažvydas were extensively investigated, defining their significance for linguistic science, cultural history, and the expansion of literature, and showing the historical development of Lithuanian book publishing.
Keywords: -